A descriptive study on the morphometric aspects of the articular facets for the talus in the human calcanei - Vrushali Sachin Bhandare; Supriya Sarjerao Methepatil (National Journal of Clinical Anatomy, 2024)
Background: Subtalar joints stability is greatly dependent on the facets on the calcaneus for talus articulation. Understanding the various variances in these features will help clinicians develop a more effective and individualized strategy that will yield the greatest outcomes. Our study aimed to examine the morphometry and morphology of the articular facets for the talus on the calcanei in humans. Methodology: In the present descriptive study, an analysis was conducted on 300 calcanei, dry bones of human adults of undetermined sex and age. The facet on every calcaneus for articulation with the talus was studied meticulously. Statistical analysis was done to determine the percentage and P value. Results: In the present study out of 300 calcanei studied, type IB with a nonconstricted articular facet pattern was found in 49.67% of calcanei, followed by type I A with a constricted articular facet present in 27% of calcanei. This was followed by type IIA in 14% of calcanei, type IIB in 5.67% of calcanei, type II C was found in only 0.67% of calcanei, type III was found in 2.33% of calcanei, and Types IV and V were found in 0.33%. Conclusion: This research elucidates the interrelationship among the articular facets of the talus and its clinical implications. Identifying distinct facet types is crucial for implementing suitable interventions to prevent injuries and ensure optimal joint function. Understanding the morphometric characteristics of these facets will undoubtedly aid orthopedic surgeons in managing disorders of the ankle and subtalar joints effectively.